Interactive effects of saline water and nitrogen fertilization on fruit quality and physiological parameters of brinjal (Solanum melongena L.) under drip and surface flood irrigation - SHEORAN, SEEMA; DAHIYA, RITA; PRAKASH, RAM; SHEORAN, HARDEEP SINGH; MUNJAL, RENU (Journal of Soil and Water Conservation, 2025)
Continuous growing population increases the demand for irrigation water for food security and limited availability of freshwater necessitates the use of non-conventional water resources such as brackish groundwater, saline drainage water, and treated wastewater for crop production. A field experiment was conducted during 2019-2020 to evaluate the effects of saline water and nitrogen fertilizer application on fruit quality and physiological parameters of brinjal (Solanum melongena L.) under drip (DI) and surface flood irrigation (SFI) methods. Experimental treatments included different qualities of irrigation water -canal water (S1), ECiw-2.5 dSm-1 (S2), and ECiw-5.0 dSm-1 (S3) and nitrogen (N) fertilizer levels i.e. 75% of the recommended dose of Nitrogen i.e. N1- 75% RDN, N2-100% RDN, and N3-125% RDN under two irrigation methods. At surface layer, soil salinities were 2.09 and 3.64 dSm-1in DI, whereas they were 3.59 and 5.36 dSm-1in SFI. The study findings demonstrated that brinjal fruit yield was augmented by 29.5% and 32.8% under DI with salinity levels S2 and S3, respectively, in comparison to SFI with analogous saline water treatments. Conversely, the application of saline water through the surface flood method resulted in a contrasting outcome, enhancing total phenol and ascorbic acid content by 31.5% and 12.7%, respectively, relative to the drip irrigation system. The brinjal fruit quality parameters i.e. protein and carotenoid content showed a negative response to the increasing water salinity but increased with the increasing N fertilizer levels. These results suggest that drip irrigation can be used over traditional method for better fruit yield, decreased soil salinity and improved fruit quality.